2015
DOI: 10.1007/s12098-015-1762-y
|View full text |Cite
|
Sign up to set email alerts
|

Social, Psychological and Financial Burden on Caregivers of Children with Chronic Illness: A Cross-sectional Study

Abstract: Most caregivers reported moderate depressive symptoms and mild to moderate anxiety symptoms. Cerebral palsy caused more social and financial burden on family vis-a-vis thalassemia. Social and financial burden on families of remaining diseases was comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 20 publications
9
77
0
10
Order By: Relevance
“…This, in turn, seriously limits their self-caring function (1). The study of Khana et al showed that the caregivers of children with cerebral palsy bear severe financial loads and face several problems including interruption and disturbance in family interactions and leisure time activities, so that their routine activities are affected by caregiving affairs (2). The findings of our study revealed that those caregivers who were responsible for caregiving for a longer period, experienced lower caregiving burden in isolation and disappointment sub-scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, seriously limits their self-caring function (1). The study of Khana et al showed that the caregivers of children with cerebral palsy bear severe financial loads and face several problems including interruption and disturbance in family interactions and leisure time activities, so that their routine activities are affected by caregiving affairs (2). The findings of our study revealed that those caregivers who were responsible for caregiving for a longer period, experienced lower caregiving burden in isolation and disappointment sub-scales.…”
Section: Discussionmentioning
confidence: 99%
“…A chronic disease refers to a condition disturbing the daily functions of people for at least three months out of a year. In another definition, it is a disease demanding hospitalization for more than one month (2). Today, advances in treatment approaches have raised the survival rate in children with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A família nuclear simples consiste em um casal e seus filhos; a monoparental simples pode ser feminina ou masculina e é organizada em torno de uma pessoa que não tem companheiro residindo na mesma casa, podendo ou não residir com os seus filhos; e a nuclear reconstituída, constituída por um casal, onde um ou ambos os cônjuges já tiveram outra união anterior, podendo ter filhos ou não. Estudos realizados com cuidadores familiares de crianças com doenças crônicas concluíram que as famílias eram, na maioria, mistas, seguidas de famílias nucleares (19) ou, ainda, formadas por marido, companheiros e demais membros, e que as mudanças na estrutura estão relacionadas à situação de doença do filho (2) . O perfil das famílias brasileiras, segundo o IBGE, mostra que o arranjo familiar comum continua a ser o de casais com filhos em 55% das famílias.…”
Section: Resultsunclassified
“…Além dessa classificação, estão no ciclo vital "Famílias com adolescentes". Estudo apontou que a maioria das mães/cuidadoras tem, em média, dois filhos com idades médias de seis anos (5,19) . A experiência da doença renal, em outros membros da família, é referida por cinco mães/cuidadoras da criança em tratamento conservador renal.…”
Section: Eu Não Tenho Ajuda Do Pai Dela Também Que Faz Uma Diferençaunclassified
See 1 more Smart Citation